INBREEDING DEPRESSION OF CAPTIVE MALAYAN GAUR (Bos gaurus hubbacki) AT JENDERAK SELATAN WILDLIFE CONSERVATION CENTRE, PAHANG - Norsyamimi, Rosli; Hartini, Ithnin; Jeffrine Japning, Rovie-Ryan (Department of Wildlife and National Parks, 2016)
The Malayan gaur or locally known as Seladang (Bos gaurus hubbacki) is the second largest terrestrial mammal in Malaysia. In Peninsular Malaysia, wild gaur can be found in considerable numbers in states of Perak, Pahang and Terengganu (Muhamad Rizal, pers. comm.). According to Conry (1981), the home range of Malayan gaur differ with sex and age. Conry (1981) calculated the home range of a herd in Lepar River Valley (central Pahang) and he found that adult male have an estimated home range of 7,018 ha, adult female with 5,213 ha, and yearling male had a home range of 2,989 ha. Gaur food preference was affected by elevation from sea level (increase in elevation limit choice of food) and types of habitat (i.e. primary forest, secondary forest, agricultural area) within their home range (Ebil, 1982, 2009). Gaur preferred 17 species of shrubs and six species of grasses (Ebil, 2009). According to Ebil (2009) the most preferred shrubs based on habitat are Shorea acuminata (primary forest), Melastoma malabathricum (secondary forest), Erythrina variegata (agricultural area) and as for grasses species, the gaur favour Imperata cylindrica (primary forest), Paspalum conjugatum (secondary forest), and Paspalum vaginatum (agricultural area).